Body Mass Index and Treatment Outcomes in Metastatic Breast Cancer Patients Treated With Eribulin. Issue 5 (20th November 2015) - Barba, Maddalena; Pizzuti, Laura; Sperduti, Isabella; Natoli, Clara; Gamucci, Teresa; Sergi, Domenico; Di Lauro, Luigi; Moscetti, Luca; Izzo, Fiorentino; Rinaldi, Massimo; Mentuccia, Lucia; Vaccaro, Angela; et al.
Abstract : Eribulin has shown survival advantage and manageable toxicity in heavily pre‐treated metastatic breast cancer (mBC). We assessed whether body mass index (BMI) impacts treatment outcomes in 101 patients treated with eribulin at six Italian Oncologic Centers. BMI was addressed as a categorical variable (18.5–24.9 vs. at least 25). Clinical benefit rate (CBR) was assessed overall and in subgroups defined by BMI, line of therapy (LOT), and hormone receptor (HR) status. Analysis of CBR by LOT and HR status were further stratified by BMI. Survival curves were compared using the Kaplan–Meier method and log‐rank test. Predictors of survival were tested in Cox models. Patients treated with eribulin as third line showed greater CBR when their BMI was in the lowest category (77.8 vs. 58.1%, P  = 0.03). Median progression free survival (PFS) and overall survival (OS) in normal and overweight patients were 4 (95% CI, 3–5) versus 3 (2.1–4) months, P  = 0.02 and 13 (11–15) versus 12 (6–18) months, P  = 0.96, respectively. Median PFS and OS in estrogen receptor (ER) positive and negative tumours were 4 (3–5) versus 3 (2–4) months, P  = 0.005 and 14 (10–18) versus 7 (4–10), P  = 0.02, respectively. In multivariate analyses, BMI impacted PFS at a nearly significant extent ( P  = 0.05), while ER expression significantly affected PFS and OS ( P  = 0.01 and 0.02, respectively). No relevant findings emerged concerning toxicity. We found evidence of greater efficacy of eribulin in leaner mBC patients, particularly if given as third line and in ER positive tumors. Further studies are warranted to confirm our findings. J. Cell. Physiol. 231: 986–991, 2016. © 2015 Wiley Periodicals, Inc.